Case Study-Based Learning Planning Strategies to Enhance Student Engagement in Elementary Schools: A Literature Review - Muhammad Sirodjuddin; Purnawirawansa Putra; Muhammad Basyaruddin; Risdah Lenah; Tiyas prastiwi; Ulfa Khasanah (Universitas Palangka Raya, 2026)
Student engagement remains a critical determinant of academic success in elementary education, yet traditional instructional approaches often fail to sustain meaningful participation. This narrative literature review synthesizes contemporary evidence (2020–2026) on the strategic planning of Case-Based Learning (CBL) and its impact on multidimensional student engagement in primary schools. Using Google Scholar as the primary database, peer-reviewed studies were screened and thematically analyzed to identify core planning components, engagement outcomes, and contextual implementation factors. The synthesis revealed five essential instructional design elements: developmentally appropriate case selection, structured scaffolding, explicit curriculum alignment, adequate temporal allocation, and authentic assessment. Empirical findings consistently demonstrate that well-planned CBL significantly enhances behavioral participation, cognitive deepening, and affective motivation among elementary learners. However, implementation success is heavily moderated by teacher pedagogical competence, institutional support, and adaptive resource utilization. These findings underscore the necessity of integrating CBL planning frameworks into teacher professional development and curriculum design. Ultimately, strategically designed case-based instruction offers a transformative pathway to reinvigorate elementary classrooms, though sustained adoption requires targeted training, flexible policies, and further longitudinal research on engagement trajectories in primary education.